PENGARUH QUALITY OF WORK LIFE DAN KECERDASAN EMOSIONALTERHADAP KINERJA KARYAWAN PT. BPR MAJALENGKA JABAR - Nita Hernita (EKBIS (Ekonomi & Bisnis), 2022)
This studi aims to determine the influice of quality of work life and emotional intelligence on the performace of employes of the PT. BPR Majalengka West Java.The research method used in this study is descriptive analysis and verification analysis. The population in this study were 64 employees of PT. BPR Majalengka West Java. The sample in this study used a saturated sampling method or census consisting of 64 employees. Data analysis using descriptive analysi, verification analysis with classic assumption test, namely normality test data, multicollinearity test, heteroscedasticity test data, multiple linear regression analysis and coefficient of determination analysis. Hypothesis testing used partial tests with t tests.Test the result of the research that quality of work life is very good category, emotional intelligence is high category and employee performance is high categor. Quality of work life has a positive and significant effect to employee performance and emotional intelligence has a positive and significant effect to employee performance.